African cotton farmers within the context of globalization : social, economic and geographical impacts. The case of Burkina Faso's Eastern region - (:unkn) unknown (My University, 2011)
The aim of this Phd is to understand the vulnerability of Burkina Faso's cotton farmers confronted to the current market and institutional changes in this economic sector. Indeed, the cotton industry has gone through a generalized crisis over the last decade - the fall in prices being the most tangible outward sign. Such an unprecedented crisis is symptomatic of the dismantling of export channels that have been introduced ever since the colonial period, under the pressure of structural adjustment policies. The cotton industry being generally acknowledged as a historical success of agricultural development, its current difficulties testify to the direct consequences of the withdrawal of both States and international cooperation from the agricultural sector. Results are based on the treatment of questionnaire surveys conducted among farmers in Eastern Burkina Faso and on half-directed interviews with all the industry participants. These field surveys are then contrasted with the strategies propounded by the cotton companies, the National Union of Burkinabe Cotton Producers and the government itself to get out of the crisis. This scale of analysis is integrated, through a multi-leveled study of the region, to the global market through the state. This multi-scalar, original approach is the only one likely to draw a productive connection between the several approaches based on a single level of analysis. Conclusions establish that the future of the cotton sector, and the stability of the area, depend on the joint actions of producers, State and international cooperation to support family farming. Finally, this study also demonstrates the interest of a geographical approach incorporating different scales of analysis as a major element of the sustainability of agricultural industries in developing countries
Keywords: African Research